Duration of culture and sonic hedgehog signaling differentially specify PV versus SST cortical interneuron fates from embryonic stem cells - Tyson, Jennifer A. (Development, 2015)
Medial ganglionic eminence (MGE)-derived GABAergic cortical interneurons (cINs) consist of multiple subtypes that are involved in many cortical functions. They also have a remarkable capacity to migrate, survive and integrate into cortical circuitry after transplantation into postnatal cortex. These features have engendered considerable interest in generating distinct subgroups of interneurons from pluripotent stem cells (PSCs) for the study of interneuron fate and function, and for the development of cell-based therapies. Although advances have been made, the capacity to generate highly enriched pools of subgroup fate-committed interneuron progenitors from PSCs has remained elusive. Previous studies have suggested that the two main MGE-derived interneuron subgroups – those expressing somatostatin (SST) and those expressing parvalbumin (PV) – are specified in the MGE from Nkx2.1-expressing progenitors at higher or lower levels of sonic hedgehog (Shh) signaling, respectively. To further explore the role of Shh and other factors in cIN fate determination, we generated a reporter line such that Nkx2.1-expressing progenitors express mCherry and postmitotic Lhx6-expressing MGE-derived interneurons express GFP. Manipulations of Shh exposure and time in culture influenced the subgroup fates of ESC-derived interneurons. Exposure to higher Shh levels, and collecting GFP-expressing precursors at 12 days in culture, resulted in the strongest enrichment for SST interneurons over those expressing PV, whereas the strongest enrichment for PV interneurons was produced by lower Shh and by collecting mCherry-expressing cells after 17 days in culture. These findings confirm that fate determination of cIN subgroups is crucially influenced by Shh signaling, and provide a system for the further study of interneuron fate and function.